From Disruption to Recovery: A global Perspective (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
There is no doubt that the global pandemic has disrupted many aspects of life, including higher education and its complex and rigid structures. The disruption of university functions and the transition from in person to virtual instruction has revealed deficiencies and posed logistical and pedagogical challenges. However, the Pandemic has also led to popular and scholarly discussions about innovation and ways of reimagining the university of the future. This short essay, provides a global perspective of such disruption and sheds light on the role of IT in creating space for resilience and innovation.